Rol del profesional de enfermería en la prevención de trastornos alimentarios en adolescentes del octavo año básica de la Unidad Educativa Emigdio Esparza Moreno, Cantón Babahoyo, mayo-septiembre 2019. - Murillo Zuñiga, Shirley Karina (2019)
This research project deals with the role of the nursing professional in the prevention of eating disorders in adolescents of the eighth basic year of the educational unit “Emigdio Esparza Moreno”, Babahoyo canton, May-September 2019, will teach us to know about the problem of disorders food, the management of this problem by the role of the nursing professional that will allow us to know about it, the relationship between both variables and their importance during the school stage where they do not have food control, tend to feed at inappropriate times and hence Part the problem. The modality of this research is quantitative and qualitative, of a correlational explanatory type, of cross-sectional purpose, with the objective of determining the prevention of eating disorders in adolescents of the eighth basic year of the educational unit “Emigdio Esparza Moreno”, Babahoyo canton, May-September 2019. Applying a rigorous methodology that allows data collection in order to obtain real and reliable data. Through this research work it is concluded that the professional role of nursing prevention activity if it influences school performance, it is determined that one of the main factors is the lack of food education by adolescents and the treatment of prevention of the eating disorders of the nursing staff of the health center responsible for attending schoolchildren, as well as the lack of knowledge of teachers about recommended physical education and feeding schedules, where adolescents at that time better nourish adolescents in the school stage.